Systematic engineering of Saccharomyces cerevisiae for D-lactic acid production with near theoretical yield. Issue 4 (15th April 2021) - Watcharawipas, Akaraphol; Sae-tang, Kittapong; Sansatchanon, Kitisak; Sudying, Pipat; Boonchoo, Kriengsak; Tanapongpipat, Sutipa; Kocharin, Kanokarn; Runguphan, Weerawat
Abstract: D-lactic acid is a chiral three-carbon organic acid that can improve the thermostability of polylactic acid. Here, we systematically engineered Saccharomyces cerevisiae to produce D-lactic acid from glucose, a renewable carbon source, at near theoretical yield. Specifically, we screened D-lactate dehydrogenase (DLDH) variants from lactic acid bacteria in three different genera and identified the Leuconostoc pseudomesenteroides variant ( Lp DLDH) as having the highest activity in yeast. We then screened single-gene deletions to minimize the production of the side products ethanol and glycerol as well as prevent the conversion of D-lactic acid back to pyruvate. Based on the results of the DLDH screening and the single-gene deletions, we created a strain called ASc-d789M which overexpresses Lp DLDH and contains deletions in glycerol pathway genes GPD1 and GPD2 and lactate dehydrogenase gene DLD1, as well as downregulation of ethanol pathway gene ADH1 using the L-methionine repressible promoter to minimize impact on growth. ASc-d789M produces D-lactic acid at a titer of 17.09 g/L in shake-flasks (yield of 0.89 g/g glucose consumed or 89% of the theoretical yield). Fed-batch fermentation resulted in D-lactic acid titer of 40.03 g/L (yield of 0.81 g/g glucose consumed). Altogether, our work represents progress towards efficient microbial production of D-lactic acid. Abstract : Rational engineering of Saccharomyces cerevisiae to produce D-lactic acid from glucose with near theoretical yield.